Implementing steroid profiling by liquid chromatography‐tandem mass spectrometry improves newborn screening for congenital adrenal hyperplasia in New Zealand. (31st January 2021) - de Hora, Mark R.; Heather, Natasha L.; Patel, Tejal; Bresnahan, Lauren G.; Webster, Dianne; Hofman, Paul L.
Abstract: Objective: To evaluate the impact of a liquid chromatography‐tandem mass spectrometry (LCMSMS) second‐tier test on newborn screening for congenital adrenal hyperplasia due to 21‐hydroxylase deficiency (CAH) in New Zealand. Design: In a prospective study, a LCMSMS method to measure 17‐hydroxyprogesterone (17OHP) was adapted to measure four additional steroids. Steroid concentrations were collected on all second‐tier CAH screening tests while protocols remained unchanged. Steroid ratio parameters with recommended or published screening cuts‐offs were evaluated for their impact on newborn screening performance. Measurements: Precision, accuracy, linearity and recovery of the second‐tier LCMSMS method were evaluated. Second‐tier specimens were divided in 3 groups; newborn screening bloodspots from neonates with confirmed CAH (n = 7) and 2 groups specimens from neonates with a birthweight (BW) ≤1500 g (n = 795) and with a BW > 1500 g (n = 806) with a negative newborn screening test. Six protocols using four steroid ratio parameters were evaluated. The sensitivity, specificity, false positive rate and positive predictive value of screening was calculated for each protocol. Results: The LCMSMS method was sufficiently accurate and precise to be used as a second‐tier test for CAH. Screening sensitivity remained at 100% for each protocol apart from (17OHP + androstenedione)/cortisol when the highest cut‐off of 3.75 was applied. The false positive rate was significantly improved when (17OHP + androstenedione)/cortisol and (17OHP + 21‐deoxycortisol)/cortisol were evaluated with cut‐offs of 2.5 and 1.5 respectively ( P  < .01) and both with a positive predictive value of 64%. Conclusions: A second‐tier LCMSMS newborn screening test for CAH offers significant improvements to screening specificity without any other changes to screening protocols.